El saque de esquina como indicador de rendimiento en fútbol. Una revisión empírica - Maneiro Dios, R.; Arda Suarez, A.; Losada Lopez, J. L.; Casal Sanjurjo, C. A.; Rial Boubeta, A. (Revista Ciencia del Deporte, 2017)
The present manuscript consists in a deep revision on the quantitative and qualitative studies related to the effectiveness of the corners in football. We have consulted five of the most internationally recognized databases, Google Scholar, PubMed, SPORTDiscus, Scopus and Web of Science. The criterion for the selection of the descriptors and the search period was aimed at accessing the main empirical works that included corner kicks. The main objective is to reach a deeper knowledge (and with the adequate empirical support) of the corner kicks in soccer. The results have been classified into three sections: 1) On a descriptive level, to know the regularity, influence and incidence of these actions in current football; 2) know the statistically significant variables associated with success in this type of actions; 3) Finally, to know and analyze the studies that collect different explanatory models (multivariate analysis). Finally, practical guidelines derived from the results of the reviewed research that can contribute to the optimization of this type of actions in professional football are presented.